2008
DOI: 10.1002/jcb.21967
|View full text |Cite
|
Sign up to set email alerts
|

Human stem cells for modeling neurological disorders: Accelerating the drug discovery pipeline

Abstract: The availability of human stem cells heralds a new era for modeling normal and pathologic tissues and developing therapeutics. For example, the in vitro recapitulation of normal and aberrant neurogenesis holds significant promise as a tool for de novo modeling of neurodevelopmental and neurodegenerative diseases. Translational applications include deciphering brain development, function, pathologies, traditional medications, and drug discovery for novel pharmacotherapeutics. For the latter, human stem cell-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Embryonic stem cells (ESCs) are derived from the inner cell mass of growing blastocysts and have been widely used in developmental biology, drug discovery and cell therapies (Crook and Kobayashi, 2008;Kirouac and Zandstra, 2008). Neural induction from ESCs is regulated by many transcription factors and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) are derived from the inner cell mass of growing blastocysts and have been widely used in developmental biology, drug discovery and cell therapies (Crook and Kobayashi, 2008;Kirouac and Zandstra, 2008). Neural induction from ESCs is regulated by many transcription factors and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Crook and Kobayashi proposed that the traditional inefficiencies, high attrition rates, protracted R&D cycles, and elevated costs inherent to drug development can be curtailed by using relatively inexpensive and high-throughput in vitro human stem cell-based assays as a first phase of discovery and preclinical development in the pharmaceutical pipeline (Crook and Kobayashi, 2008). iPS cells can be used to improve the efficiency of novel drug discovery by providing disease-and patient-specific cells with particular gene expression profile.…”
Section: Establishment Of Disease Modelsmentioning
confidence: 99%
“…This is because sporadic diseases may be caused by epigenetic changes to cells that are subsequently removed through reprogramming (Ebert and Svendsen, 2010). While the method of reprogramming is likely to be less of an issue for disease modeling and drug discovery, it remains to be shown that viral integration and transduction of foreign genes does not confound endogenous cellular processes (Crook and Kobayashi, 2008).…”
Section: Establishment Of Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicologists have employed Embryonic Stem Cells (ESCs) to investigate the genotoxic effects of environmental pollutants (Chan 2008;Vinoth et al 2008). In the pharmaceutical industry, stem cell-based assays been established as a low cost, high throughput approach to assess efficacy and toxicity in the early stages of drug development (Crook and Kobayashi 2008). Most importantly, stem cells have been exploited as in vitro models of differentiation.…”
Section: Introductionmentioning
confidence: 99%